2016
DOI: 10.1128/jcm.02813-15
|View full text |Cite
|
Sign up to set email alerts
|

Plasmalyte: No Longer a Culprit in Causing False-Positive Galactomannan Test Results

Abstract: dFalse-positive galactomannan (GM) results have been reported in patients treated with gluconate-containing solutions, such as Plasmalyte. The GM optical density index was tested on 33 distinct batches of Plasmalyte and was found to be negative in all of the batches, confirming that Plasmalyte is no longer a cause of false-positive GM results. Invasive aspergillosis is a serious infection associated with a high mortality rate in patients at risk, such as those receiving chemotherapy or undergoing allogeneic he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 11 publications
2
12
0
Order By: Relevance
“…False‐positive GM antigenemia is reported in haematological patients after allogeneic PBSCT due to gastrointestinal chronic GvHD . However, recent publications regarding GM in beta‐lactam antibiotics and sodium gluconate could not detect GM anymore . Furthermore, false‐positive GM EIA results due to TZP or PN infusion did not occur in our investigation which is consistent with the results of our previous in vitro study .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…False‐positive GM antigenemia is reported in haematological patients after allogeneic PBSCT due to gastrointestinal chronic GvHD . However, recent publications regarding GM in beta‐lactam antibiotics and sodium gluconate could not detect GM anymore . Furthermore, false‐positive GM EIA results due to TZP or PN infusion did not occur in our investigation which is consistent with the results of our previous in vitro study .…”
Section: Discussionsupporting
confidence: 90%
“…26 However, recent publications regarding GM in beta-lactam antibiotics and sodium gluconate could not detect GM anymore. [13][14][15][16][17][18]27,28 Furthermore, false-positive GM EIA results due to TZP or PN infusion did not occur in our investigation which is consistent with the results of our previous in vitro study. 7 In contrast, Recommendations to the handling of false positivity exist only for the GM EIA.…”
Section: Kinetic Analysissupporting
confidence: 92%
“…Positive test results in patients receiving PL 148 should therefore be interpreted cautiously and the galactomannan antigen should be confirmed by other diagnostic methods[4]. More recently however, Spriet et al[8] tested 33 distinct batches of PL 148 and reported that with contemporary sophisticated manufacturing processes, PL 148 does not result in false-positive galactomannan test results.…”
Section: Discussionmentioning
confidence: 99%
“…Bronchoalveolar lavage galactomannan is more sensitive than serum GM in diagnosing probable or proven IA, likely due to a higher fungal burden in the airways than in the blood in IA, and increased secretion of GM in lung tissue . False positive BAL‐GM results occur in immunocompetent patients colonised with Aspergillus without clinical or radiographic evidence of IA, and potentially in patients receiving piperacillin‐tazobactam or gluconate‐containing solutions containing GM antigens; this is no longer a major concern due to changes in manufacturing . Occasionally, BAL‐GM may be positive in infections with other non‐ Aspergillus fungi .…”
Section: Introductionmentioning
confidence: 99%
“…7,10 False positive BAL-GM results occur in immunocompetent patients colonised with Aspergillus without clinical or radiographic evidence of IA, 11 and potentially in patients receiving piperacillin-tazobactam or gluconate-containing solutions containing GM antigens; this is no longer a major concern due to changes in manufacturing. [12][13][14] Occasionally, BAL-GM may be positive in infections with other non-Aspergillus fungi. 15 False negative results have been reported in patients receiving antifungal agents.…”
Section: Introductionmentioning
confidence: 99%